Renal involvement in sarcoidosis: histological patterns and prognosis, an Italian survey.: Renal involvement in sarcoidosis. - Rastelli, Francesco; Baragetti, Ivano; Buzzi, Laura; Ferrario, Francesca; Benozzi, Luisa; Di Nardo, Francesco; Devoti, Elisabetta; Cancarini, Giovanni; Mezzina, Nicoletta; Napodano, Pietro; Gallieni, Maurizio; Santoro, Domenico; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Granulomatous interstitial nephritis in sarcoidosis (sGIN) is generally clinically silent, but in